A Systematic Review of Integrated Functional Near-Infrared Spectroscopy (fNIRS) and Transcranial Magnetic Stimulation (TMS) Studies - Curtin, Adrian; Tong, Shanbao; Sun, Junfeng; Wang, Jijun; Onaral, Banu; Ayaz, Hasan (Frontiers in Neuroscience, 2019)
Background The capacity for TMS to elicit neural activity, manipulate and produce measures of cortical excitability has created significant expectation regarding its use in both cognitive and clinical neuroscience. However, the absence of the ability to quantify stimulation effects, particularly outside of the motor cortex, has led clinicians and researchers to pair noninvasive brain stimulation with noninvasive neuroimaging techniques. FNIRS as an optical and wearable neuroimaging technique is an ideal candidate for integrated use with TMS. Together, TMS+fNIRS may offer an alternative to “blind” stimulation as a hybrid methodology to assess NIBS in therapy and research. Objective In this systematic review, the current body of research into the transient and prolonged effect of TMS on fNIRS-based cortical hemodynamic measures while at rest and during tasks are discussed. Additionally, studies investigating the relation of fNIRS to measures of cortical excitability as produced by TMS-evoked Motor-Evoked-Potential (MEP) are evaluated. The aim of this review is to outline the integrated use of TMS+fNIRS and consolidate findings related to use of fNIRS to monitor changes attributed to TMS and the relationship of fNIRS to cortical excitability itself. Methods Key terms were searched in PubMed and Web-of-Science to identify studies investigating the use of both fNIRS and TMS. Works from Google-Scholar and referenced works in identified papers were also assessed for relevance. All published experimental studies using both fNIRS and TMS techniques in the study methodology were included. Results A combined literature search of neuroimaging and neurostimulation studies identified 53 papers detailing the joint use of fNIRS and TMS. 22/53 investigated the immediate effects of TMS at rest in the DLPFC and M1 as measured by fNIRS. 21/22 studies reported a significant effect in [HbO] for 40/54 stimulation conditions with 14 resulting an increase and 26 decrease. While 15/22 studies also reported [HbR], only 5/37 conditions were significant. The fNIRS+TMS for tasks were detailed in 16 studies, including 10 with clinical populations. Most studies only reported significant changes in [HbO] related measures. Studies comparing fNIRS to changes in MEP-measured cortical excitability suggest that fNIRS measures may be spatially more diffuse but share similar traits.